OBEDIENCE PREDICTOR USING SELF PROTECTIVE EQUIPMENT AT PT MEGA ANDALAN KALASAN - prasetyawati prasetyawati (Universitas Darussalam Gontor, 2019)
Personality is a distinctive part of each individual. This is what distinguishes one individual from another. Personality is an individual characteristic with consistent patterns of behavior, feelings and thoughts. This study aims to determine the effect of employee personality types on compliance using PPE with additional internal and external variables. Personality (sanguinis, melancholy, kolerik and plegmatis), age, education, knowledge, and comfort of PPE were analyzed as independent variables and compliance using PPE as a dependent variable. The personality definition used is personality plus in Littauer with four personality types namely Sanguinis, Kolerik, Melancholy and Plegmatis. This study has a quantitative research approach, with observational research types. The design of this research is cross sectional study. This research was conducted at PT Mega Andalan Kalasan (MAK), Yogyakarta. This research sample amounted to 92 workers with sampling technique using stratified random sampling technique. Based on the chi-square test with the results of p-value 0.011, which means that it shows a significant relationship between personality types with compliance using PPE. In addition, age also shows significant results. Conclusion: Type of personality and age affect the use of PPE in workers at PT. MAK. Keywords: Personality, Obedience, Personal Protective Equipment